Business Activity Organization on the Regional Level: State and Prospects - HARKUSHA, Serhii Anatoliyovych; HLUSHACHENKO, Anatoliy Ivanovych; DOVZHYK, Olena Oleksandrivna (Journal of Advanced Research in Law and Economics, 2017)
This article describes the process of business activity organization on the regional level and possible influence that external factors cause on it. It is stated that in the years 2010-2015 the number of economic entities in Ukraine has slightly decreased. It is concluded that the share of all the types of enterprises is similar in Ukraine comparing with the EU averages, although there is a significant deviation in the indices of businesses by 10 thousand populations which in Ukraine are less than the average for EU countries. In the process of researching the state of development of business activity and the problems of SME development are being indicated. The problems include the following: lack of business support programs at the national level; inconsistency of bank lending to the requirements of business (high interest rates); insufficient infrastructure to support business; unsatisfactory state of vocational training; lack of seed capital for business creation; lack of working capital for business development. It’s concluded that the business model of any business activity plays the role of a template in the process of creation and operation of business in the certain circumstances. It also is an important step in the strategic planning, which includes an overview of future business that in turn affects the evaluation of the main keys of success of the enterprise and determines its growth. The model of business creation is relatively based on resource approach, which is concentrated on the resources and capabilities of the enterprise and is the most important for determining strategic actions. In the perfect circumstances the resources for business activity are meant to become the part of the process of business creation and development. They may be helpful not only as route map of the project implementing but also as its main part. The issue of developing the set of measures that provide the specific tasks of development and activity of small and medium enterprises at the regional level that will ensure efficient use of any information and implementation of scientific approach in business was further developed. The measures mentioned include: implementing the support of entrepreneurship; microcredit funding of the SMEs; increasing the number of small and medium-sized businesses in the production and others. The article also states that business is entirely dependent on the state system concept. The set of measures that provide specific tasks of development and activity of small and medium enterprises (stimulation of entrepreneurship, attracting business in the IT sector, the promotion of export-oriented businesses) should not only solve the economic problems of the country and the region but social issues as well: providing more working places and supporting the small business in the regions. The research and conclusions gained in this article may be used as the theoretical and practical material for government in order to support the SMEs and for entrepreneurs who intend to start their own business.